Literatur Review: Pengaruh Jenis dan Posisi Substituen terhadap Keasaman Asam Benzoat dan Turunannya - Ni Luh Putu Yuniantari; Erlin Susilowati (Yayasan Literasi Sains Indonesia, 2025)
Benzoic acid is an aromatic compound (C7H6O2), was found in plant and animal tissues, and also be produced from the fermentation process of microbial metabolism. Benzoic acid and its derivatives are widely used in agriculture, health and food. Because it’s functional, the reactivity of benzoic acid and its derivatives must be understood. One of the reactivity of benzoic acid is acidity. Acidity of benzoic acid is used to predicted reaction mechanism. Focus of this research is analysis the acidity of benzoic acid and its derivatives based on resonance theory and the effect of EWG (electron withdrawing groups) and DG (donating groups) to its acidity. The data in this research is collect by literature review on November 2024. In this research, it was found that the acidity of the benzoic acid and its derivatives was influenced by the type and position of the substituent. If the substituent is EWG, the acidity is increase and when substituent is DG, the acidity is decrease. These data can be explained by resonance.